Strategy of the Public Relations Division of the Sidoarjo Regency DPRD Secretariat in Enhancing A Positive Image in the Community - Bella Putri Julianti; Sarah Meirina Sari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The formation of a positive image of a public institution is not only determined by the quality of its performance, but also by the way the institutional message is formulated and conveyed to the public. This is reflected in the strategic role of the Public Relations Division of the Sidoarjo Regency DPRD Secretariat in managing public perception through publications of council activities, media relations, and responses to sensitive issues. The dynamics of regional politics, demands for transparency, and public criticism and demonstrations make the public relations function crucial in maintaining legitimacy and public trust. This study aims to analyze the communication strategy of the Public Relations Division of the Sidoarjo Regency DPRD Secretariat and the application of linear communication and symmetrical two-way communication in public relations practices. The method used is a descriptive qualitative approach through in-depth interviews, observations, and documentation studies. The results show that linear communication is implemented through routine publications on social media, official websites, and e-clippings to maintain information consistency. Meanwhile, symmetrical two-way communication is used in responding to criticism and public issues through open dialogue and clarification. This hybrid communication strategy has been proven to strengthen public trust and a positive image of the Sidoarjo Regency DPRD